Oracle PL/SQL performance tuning tips & techniques - Rosenblum, Michael; Dorsey, Paul (New York : McGraw-Hill Education, 2014)
"In Oracle PL/SQL Performance Tuning Tips & Techniques, Oracle ACE authors with decades of experience building complex production systems for government, industry, and educational organizations present a hands-on approach to enabling optimal results from PL/SQL. The book begins by describing the discovery process required to pinpoint performance problems and then provides measurable and repeatable test cases. In-depth coverage of linking SQL and PL/SQL is followed by deep dives into essential Oracle Database performance tuning tools. Real-world examples and best practices are included throughout this Oracle Press guide"--
The role of PL/SQL in contemporary development -- DBA/Developer Borderline: tools and features -- Code instrumentation in PL/SQL -- Expanding the SQL horizons -- Thinking in sets -- Pulling the trigger -- Going beyond scalar dataypes -- Keepind the cache -- Shooting at a moving target -- Tales from the trenches -- Code management in real-world systems -- Extra tips, tricks, and ideas.
Keywords: SQL/ORACLE (Computer program language); PL/I (Computer program language)